KAMPUNG INGGRIS DI LINGKUP SEKOLAH SEBAGAI PRASARANA ALTERNATIF PEMBELAJARAN BAHASA INGGRIS INTENSIF SCHOOL-BASED ENGLISH CAMP AS AN ALTERNATIVE MEANS ON LEARNING ENGLISH INTENSIVELY - Arining Wibowo (JURNAL ILMIAH BAHASA DAN SASTRA, 2015)
This paper is constructed based on the research about the effect of the English camp program to the students’ interest on learning English. English Camp is also known as ‘Kampung Inggris’. This research is held in Islamic Senior High School (Madrasah Aliyah) Al-Itihad Poncokusumo Malang, East Java. English kampong is the term adapted from the program famously- exist in Pare Kediri, East Java. Look at the big intention of people in East Java on following English short course in Pare, then became an inspirational system to the researcher on adapting the system but in different method that; English Camp is held in school. Therefore, with the method students will be easily increase their language competence by following English Camp in their school without hard effort. On this research will be explained some research result in-correlation to the English Camp held in M.A Al-Itihad Poncokusumo Malang and its effects to the students’ interest on following English Camp program. The method used is the descriptive-correlation, that is the method by which the researcher explain the fact found and measure its correlation to the variables on the research. The result of this research shows that English Camp impact positively and extensively to increase the students’ language competence. The most prominent indication is shown from the students’ big interest on learning English. From the data analysis by Pearson Product Moment method and followed by T-test, we got a fact that English Camp could give effect up to 80% to increase the students’ learning English interest which it will be automatically improve their language competence.